Karakteristik Facade Rumah Toko di Kawasan Pasar Hongkong di Kota Singkawang - Puspito Harimurti; Muhammad Radhi; Chandra Bayu (Politeknik Negeri Pontianak, 2021)
The city of Singkawang, which is located on the west coast of the island of Borneo, is thought to have existed around the 18th century, and has links to a gold mining center managed by gold miners from Chinese origin in Monterado. The Central Government together with the City Government of Singkawang, have designated Singkawang City as one of the Heritage Cities in Indonesia, through the RTBL City Pusaka program in 2016. The Hong Kong Market area is one of the blocks for the Heritage City of Singkawang, centered on Jalan Setia Budi and Jalan Bawal . The Hong Kong Singkawang Market is one of the centers of nighttime activities in Singkawang City The purpose of this research is to carry out an inventory and identification of the typical characteristics of shop houses (RUKO) in the Hongkong Market area in Singkawang City, and to identify the diversity of façade displays of Chinatown shophouses in Singkawang through a study of the building typology and the changing pattern of its façade. This study uses a qualitative-rationalistic approach with a descriptive-qualitative approach to the typology of shophouses in the Pasar Hongkong area in Singkawang City. The descriptive research flow starts from units of information or objects of observation which gradually, the findings are dialoged (abstracted) to compile general themes which at the end of the abstraction process, can produce a final finding in the form of a local theory (character and typology of shop houses in the Pasar area. Hong Kong in the City of Singkawang). The Technology Absorption Rate (TKT) of this applied research is at level 4, which is a prototype of a heritage building data collection system in Singkawang City. The form of this research analysis is to use a descriptive approach